1995
DOI: 10.1080/10473289.1995.10467342
|View full text |Cite
|
Sign up to set email alerts
|

Determining Temporal and Spatial Variations in Ozone Air Quality

Abstract: Unless the change in emissions is substantial, the resulting improvement in ozone air quality can be easily masked by the meteorological variability. Therefore, the meteorological and chemical signals must be separated in examining ozone trends. In this paper, we discuss the use of the Kolmogorov-Zurbenko filter in evaluating the temporal and spatial variations in ozone air quality utilizing ozone concentration data from several monitoring locations in the northeastern United States. The results indicate a dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 1 publication
2
35
1
2
Order By: Relevance
“…Similarly diverse applications have been seen in studies of water pollution ( e.g., Baker et al, 1978;Lebowitz et al, 1992;Rao et al, 1995 ) and hazardous waste (e.g., Lagakos et al, 1986;Lampi et al, 1992;Gamble and Lewis, 1996;Molholland et al, 1998 ). Exposure indicators using residence location are easy and inexpensive to construct, and increased use is anticipated given advances in geographic information systems (GIS ) and databases that simplify identification of potentially polluted areas (Clark et al, 1982;Budnick et al, 1984;Geschwind et al, 1992;Dayal et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly diverse applications have been seen in studies of water pollution ( e.g., Baker et al, 1978;Lebowitz et al, 1992;Rao et al, 1995 ) and hazardous waste (e.g., Lagakos et al, 1986;Lampi et al, 1992;Gamble and Lewis, 1996;Molholland et al, 1998 ). Exposure indicators using residence location are easy and inexpensive to construct, and increased use is anticipated given advances in geographic information systems (GIS ) and databases that simplify identification of potentially polluted areas (Clark et al, 1982;Budnick et al, 1984;Geschwind et al, 1992;Dayal et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have indicated this is indeed the case. Ding et al (2008) analyzed O 3 data from the MOZAIC (measurement of ozone and water vapor by Airbus in-service aircraft) program and obtained a 2 % year −1 rate of increase in the daytime O 3 in the lower troposphere over Beijing and its surrounding areas for the period of 1995-2005 analyzed the TOR (tropospheric ozone residue) data over the period 1979-2005 and found a significant upward trend in tropospheric O 3 over the North China Plain for all seasons except for winter, with a maximum rate of increase of 1.10 DU per decade for summer. Wang et al (2009) found that surface O 3 at a regional station in Hong Kong increased at an average rate of 0.58 ppb year −1 from 1994 to 2007 and they associated the trend with an increase in tropospheric NO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]11,12 Several studies have used Pearson correlation coefficients to characterize spatial variability in ambient air pollutant concentrations. [13][14][15][16][17] Other studies have used analysis of variance to characterize variability in air pollutant concentrations between specific monitoring sites. 18 -20 Analysis of variance provides a measure of variation between monitoring sites relative to variation over time at one monitoring site and is particularly useful when several sites with different average concentrations are considered.…”
Section: Introductionmentioning
confidence: 99%